Empowering the health workforce to make the most of the digital revolution - Socha-Dietrich, Karolina (OECD Publishing, 2021)
Digital technologies offer unique opportunities to strengthen health systems. However, the digital infrastructure only provide the tools, which on their own cannot transform the health systems, but need to be put to productive use by health workers. This report discusses how to engage and empower the health workforce to make the most of the digital revolution. While many health workers already use some digital tools and perceive the benefits that they bring to them and to patients, many also question the value digital technologies produce in health care or complain about technology getting in the way of work. Moreover, health workers often report not having sufficient opportunities for the up-skilling required to fully use new technologies or that the legal, financial, and organisational aspects of work - designed in the pre-digital era - do not enable them to reap the full benefits of these new technologies. Health workers and patients also demand appropriate safeguards against possible lack of transparency or threats to data privacy
Keywords: Social Issues/Migration/Health; Science and Technology